Fuzzy based Power Flow control of Two Area Power System - K Manickavasagan (International Journal of Electrical and Computer Engineering (IJECE), 2012)
This paper deals with the novel approach of fuzzy based power flow control of two area power system. Interconnected operation enables utilities to share the generation from one area to other areas. In each area, all the generators are synchronized at same frequency. The change in system load within the area causes frequency deviation in the generating buses and tie line error in the tie lines connecting neighboring areas. The control of interconnected power system is achieved by Automatic Generation Control (AGC), which maintains the balance between generation and load. In this paper, the components of AGC, frequency deviation (DF), tie line error (DPtie) and the output change in generations (DPgi) are calculated by steady state power flow analysis using decoupled Newton Raphson method. The control action is performed by conventional method using participation factor and Fuzzy Logic Controller (FLC). The DF and DPtie are the inputs to the conventional controller and Fuzzy Logic Controller (FLC). The proposed method is tested with modified IEEE 30 bus system and the results are compared. Analysis reveals that FLC is quite capable of suppressing the frequency deviation and tie line error effectively as compared to that obtained with conventional controller.DOI:http://dx.doi.org/10.11591/ijece.v2i1.219